(untitled) (Innovative professional education, 2025)
The article proves the effectiveness of integrated lessons in the modern educational process, especially with the use of digital technologies. It emphasizes that such lessons contribute to the formation of a holistic worldview among students, the development of critical thinking, and practical skills. Special attention is given to the integration of physics and the Ukrainian language through the example of the topic «The Atom and the Word – the Foundation of the World and Language,» which demonstrates the interconnection between these disciplines. The advantages of using digital technologies in education, such as expanding the information space, visualization, and individualized learning, are analyzed.